2020
DOI: 10.1111/jce.14806
|View full text |Cite
|
Sign up to set email alerts
|

High‐power short duration and low‐power long duration in atrial fibrillation ablation: A meta‐analysis

Abstract: Background: Multiple strategies have advocation for power titration and catheter movement during atrial fibrillation (AF) ablation. Comparative favoring evidence regarding the efficacy, logistics, and safety of a higher-power, shorter duration (HPSD) ablation strategy compared to a lower-power, longer duration (LPLD) ablation strategy is insubstantial. We performed a meta-analysis to compare arrhythmia-free survival, procedure times, and complication rates between the two strategies.Methods: We searched MEDLIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 47 publications
3
29
0
1
Order By: Relevance
“…Fifth, despite the propensity-matched comparison, there was an evolution of the mapping system, and the catheters and the ablation technique do not remain the same during the long-term period of patient inclusion. Sixth, although similar results were reported in the previous studies (39,40), this study reported outcomes including autonomic neural effects of HPSD in the large population cohort with propensity score matching. Finally, this study was an observational study and even propensity score matching could not compensate for all confounding factors such as center experience and advanced ablation technology might affect the outcome of this study.…”
Section: Limitationssupporting
confidence: 72%
“…Fifth, despite the propensity-matched comparison, there was an evolution of the mapping system, and the catheters and the ablation technique do not remain the same during the long-term period of patient inclusion. Sixth, although similar results were reported in the previous studies (39,40), this study reported outcomes including autonomic neural effects of HPSD in the large population cohort with propensity score matching. Finally, this study was an observational study and even propensity score matching could not compensate for all confounding factors such as center experience and advanced ablation technology might affect the outcome of this study.…”
Section: Limitationssupporting
confidence: 72%
“…After optimizing the contact force, there was no steam pops occurred in the following procedures [ 17 ]. One meta-analysis study concluded that the periprocedural risk is similar between conventional energy and HPSD in AF ablation [ 18 ]. Therefore, HPSD is still an effective and safe ablation strategy without increasing the periprocedural risk.…”
Section: Discussionmentioning
confidence: 99%
“…Kewcharoen et al 28 found that the more veins that had reconnected after the initial ablation, the better the outcome of the redo ablation. One of the early studies 31 of high-power ablation did not reduce the duration of RF energy application and showed that, when HPSD for long duration is utilized, there are a substantial number of unwanted complications.…”
Section: Meta-analysesmentioning
confidence: 99%